2010
DOI: 10.1007/s00128-010-0141-7
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and Occupational Exposures to Mercury Among Indigenous People in Dunkwa-On-Offin, a Small Scale Gold Mining Area in The South-West of Ghana

Abstract: Total mercury concentrations in human hair and urine samples were determined to ascertain the extent of environmental and occupational mercury exposure in Dunkwa-On-Offin, a small scale gold mining area of the central-west region of Ghana. In all ninety-four (94) hair and urine samples comprising of forty (40) small scale miners and fifty-four (54) farmers were collected and analyzed for their total mercury levels using the cold vapour atomic absorption spectrometry. The hair total mercury concentrations range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 9 publications
1
20
1
Order By: Relevance
“…Both from large‐scale industrial ore mining (Byrne et al 2012) and local artisanal small‐scale mining (Ashe 2012; Angosto‐Fernández 2019), it is another major source of pollution in IP lands. Mineral extraction activities affect IPs who are participants or workers at mines (Kwaansa‐Ansah et al 2010; Basu et al 2018), as well as in wider areas downstream from operations affected by tailings disposal, impacting indigenous water supplies (Shaw and Welford 2007; Daigle 2018). For example, the Ok Tedi mine in Papua New Guinea dumped 1 billion metric tons of tailings in local rivers used by the Yonggom (Kirsch 2007), and the Grassberg mine in Indonesian Papua has also resulted in substantial impacts upon the water resources used by the Amungme and the Kamoro peoples (Rifai‐Hasan 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Both from large‐scale industrial ore mining (Byrne et al 2012) and local artisanal small‐scale mining (Ashe 2012; Angosto‐Fernández 2019), it is another major source of pollution in IP lands. Mineral extraction activities affect IPs who are participants or workers at mines (Kwaansa‐Ansah et al 2010; Basu et al 2018), as well as in wider areas downstream from operations affected by tailings disposal, impacting indigenous water supplies (Shaw and Welford 2007; Daigle 2018). For example, the Ok Tedi mine in Papua New Guinea dumped 1 billion metric tons of tailings in local rivers used by the Yonggom (Kirsch 2007), and the Grassberg mine in Indonesian Papua has also resulted in substantial impacts upon the water resources used by the Amungme and the Kamoro peoples (Rifai‐Hasan 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Another study in Zimbabwe reported high blood-mercury concentrations, defined as >0.05 mg/l (corresponding to 50 μg/l) in 17% of a sample of 66 adult miners [ 96 ]. Miner cohorts in South West Ghana (mean of 1 μg Hg/l urine) [ 99 ], Peru (mean/median of 9 μg Hg/g creatinine) [ 100 ], Suriname (mean of 30 μg Hg/g creatinine) [ 101 ], Thailand (mean of >35 μg Hg/g creatinine) [ 102 ], and northern Tanzania (mean of nearly 40 μg Hg/g creatinine) [ 103 ] showed lower biomonitoring concentrations in miners compared to the results of this study, while higher median urine mercury concentrations (44 μg/l) were reported for amalgam smelting miners in the Upper East Region in Ghana [ 104 ]. In Venezuela and Burkina Faso the average urine mercury concentrations reached nearly 105 μg/g creatinine [ 22 ] resp.…”
Section: Discussionmentioning
confidence: 99%
“…Mercury exposure in mining communities has been well established in the literature in places such as Brazil, Indonesia, Zimbabwe, and Ghana (Global Mercury Project 2006; Kwaansa-Ansah et al 2010), but much less is known about other toxic chemicals, such as lead. Findings from this investigation should be included into existing global initiatives to address other heavy metals in addition to mercury.…”
Section: Discussionmentioning
confidence: 99%